2019
DOI: 10.1016/j.pmedr.2019.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Association of personal vehicle access with lifestyle habits and food insecurity among public housing residents

Abstract: Transportation type may play a role in the ease with which a person can access healthy food and recreation facilities. Our objective was to determine the relationship between access to a personal vehicle and diet, food insecurity, and physical activity among public housing residents, which are typically low-income, urban populations. We conducted a cross-sectional survey of randomly selected households within two public housing communities in Baltimore, MD (2014–2015). Our independent variable was whether or n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…A study documented that households with inconsistent access to utilities such as electricity or water, medical care, cooking fuel and cash had a significantly higher prevalence of severe FI [ 66 ]. Another study reported that access to a personal vehicle was inversely associated with FI [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…A study documented that households with inconsistent access to utilities such as electricity or water, medical care, cooking fuel and cash had a significantly higher prevalence of severe FI [ 66 ]. Another study reported that access to a personal vehicle was inversely associated with FI [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, our results demonstrate that a social network intervention reducing SSB consumption is acceptable, can be implemented, and produces significant decreases in added sugar intake among adult public housing residents trained as Peer Educators and their social network members. Although public housing residents are a highly impoverish population with high levels of food insecurity, 35 this study demonstrates that they can make significant dietary changes. Sugar Champ may have been effective due in part to focusing on a few salient behaviors and utilizing the natural social supports in the environment.…”
Section: Discussionmentioning
confidence: 78%
“…The unexpected change of direction in the association between a lack of toilet facility and food insecurity after adjusting for other social vulnerability indicators requires further investigation. The inverse association between lack of vehicle access and food insecurity might be indirectly linked to costs associated with vehicle ownership (such as monthly installments to purchase or lease, maintenance, and fuel), rather than the use of vehicle to access food as previously reported [ 30 ]. Within South Africa, these costs might reduce food quality and quantity.…”
Section: Discussionmentioning
confidence: 90%